Is it Possible to Keep the Exoskeleton of the Crab Callinectes Ornatus Soft for Several Days? (Global Journal of Medical Research, 2021)
Soft-shell crab is considered a gastronomic delicacy, reaching high values in the international market. Under normal conditions, the process of hardening of the crab's exoskeleton after moulting takes approximately two days to complete; however, the commercial consistency of soft-shell crab is lost in just 3 hours. The goal of this research was to evaluate the effects of chemical changes of water on the duration of postmoult, specifically at the stage in which they can be marketed as soft-shelled crab. In this research, Callinectes ornatus (n=241) underwent two experiments: One group was maintained in tanks with partial daily water renewal (Experiment 1), and other in tanks without water renewal (Experiment 2). In the experiment 1, the chemical characteristics of the water remained unchanged over time (p > 0.05), and the median time to hardening of the exoskeleton after moulting was 3 hours.
Keywords: acidification; ammonification; portunidae; calcium; moult; soft-shell crab